Sex-specific poor physical performance in Korean community-dwelling older adults - Kai Wang; Suyeon Kim; Taehyun Song; Seongryu Bae; Hyuntae Park; S. Jun Son (Experimental Gerontology)
Background: Poor physical performance appears to be different across age and sex. The aim of this study was to examine changes in physical performance across age groups by sex. Methods: A cross-sectional study was conducted with 292 community-dwelling older adults (144 males, 148 females; age: 74.7 ± 5.2 years, body mass index: 23.8 ± 2.7 kg/m2). Physical performance tests included (i) strength (handgrip, knee extension, ankle dorsiflexion, ankle plantarflexion, and toe grip), (ii) functional mobility (5 sit-to-stand, 4-m gait speed, and 4-m fast gait speed), and (iii) postural control (timed single-leg stance). Physical performance was compared across four different age groups by sex using ANOVA tests, T-score, and linear regression analysis. All statistical analysis was set at 0.05. Results: ANOVA showed a significant age effect (p < 0.05) on physical performance measures with only exception for ankle muscle strength. T-score and linear regression analyses revealed sex-specific trends. In males, postural control showed the most significant poor performance, followed by strength. In females, the most notable poor performance was also observed in postural control, followed by functional mobility. Conclusions: Most main outcome measures in physical performance worsened over time across age groups while poor performance pattern was different between older males (strength) and females (functional mobility). We highlighted the importance of assessing strength, functional mobility, and postural control in older adults. Based on observed poor performance patterns across age groups by sex, sex-specific interventions should be implemented.